IMPACTS OF RISING ANIMAL FOOD PRICES ON DEMAND AND POVERTY IN INDONESIA - Nikmatul Khoiriyah; Ratya Anindita; Nuhfil Hanani; Abdul Wahib Muhaimin (Socio-Economics/Agribusiness Department, 2020)
Protein deficiency is one of the causes of the poor nutritional status of the Indonesian population, is permanent, and long-term will have an impact on the lower quality of human resources. This study analyzes the impact of price and income changes on animal food consumption patterns and demand on five poverty level in Indonesia. The demand esimation uses Quadratic Almost Ideal Demand Systems, using the National Socio Economic Survey (SUSENAS) data (March 2016) compilation data of 291,414 households. The results showed that there were different interactions between beef and the other four animal protein food sources, namely the Poor, Almost Poor and Vulnerable Poor beef substitution was mainly chicken, followed by fresh fish and eggs. Hicksian's own-price elasticity decreases following the decrease in the level of household poverty. Cases of beef, household own-price elasticity